The Investigation of Different Curing Regimes on Reactive Powder Concrete Strength: A Review (Journal of Engineering, 2024)
Enhancing the properties of reactive powder concrete (RPC) by developing the internal structure or making replacements or additions to the aggregates is becoming a prevalent method to obtain RPC with desired properties, which it can be used in numerous applications in the construction industry. Pozzolanic active constituents are used in large quantities to reach the desired properties, but on the other hand, these methods are still not sustainable and could be expensive. This study explores methods of curing RPC that affect compressive strength and other mechanical properties. This study briefly describes how RPC's internal structure and mechanical properties are enhanced. The core objective of this study is to review the methods for curing RPC such as normal, hot water, steam, hot air, and autoclave curing. Curing methods significantly impact the strength of concrete. High-temperature methods, especially autoclave curing, accelerate hydration and produce superior concrete properties.